Kitkaite NiTeSe, an Ambient‐Stable Layered Dirac Semimetal with Low‐Energy Type‐II Fermions with Application Capabilities in Spintronics and Optoelectronics. (27th September 2021) - Vobornik, Ivana; Sarkar, Anan Bari; Zhang, Libo; Boukhvalov, Danil W.; Ghosh, Barun; Piliai, Lesia; Kuo, Chia‐Nung; Mondal, Debashis; Fujii, Jun; Lue, Chin Shan; Vorokhta, Mykhailo; Xing, Huaizhong; et al.
Abstract: The emergence of Dirac semimetals has stimulated growing attention, owing to the considerable technological potential arising from their peculiar exotic quantum transport related to their nontrivial topological states. Especially, materials showing type‐II Dirac fermions afford novel device functionalities enabled by anisotropic optical and magnetotransport properties. Nevertheless, real technological implementation has remained elusive so far. Definitely, in most Dirac semimetals, the Dirac point lies deep below the Fermi level, limiting technological exploitation. Here, it is shown that kitkaite (NiTeSe) represents an ideal platform for type‐II Dirac fermiology based on spin‐resolved angle‐resolved photoemission spectroscopy and density functional theory. Precisely, the existence of type‐II bulk Dirac fermions is discovered in NiTeSe around the Fermi level and the presence of topological surface states with strong (≈50%) spin polarization. By means of surface‐science experiments in near‐ambient pressure conditions, chemical inertness towards ambient gases (oxygen and water) is also demonstrated. Correspondingly, NiTeSe‐based devices without encapsulation afford long‐term efficiency, as demonstrated by the direct implementation of a NiTeSe‐based microwave receiver with a room‐temperature photocurrent of 2.8 µA at 28 GHz and more than two orders of magnitude linear dynamic range. The findings are essential to bringing to fruition type‐II Dirac fermions in photonics, spintronics, and optoelectronics. Abstract : Kitkaite (NiTeSe) is an ambient‐stable transition‐metal dichalcogenide with type‐II bulk Dirac fermions around the Fermi level and topological surface states with strong spin polarization. The high potential for optoelectronics is validated by the implementation of ultrasensitive microwave receivers.